Analysis of the Effect of Linac Determination and Institutional Coordination on Implementation Time Performance Based on Decision-Making Performance in Linac Room Construction - Adelia Rizky Fatmawati; Agus Suroso (Academia Open, 2026)
General Background: Government procurement of advanced medical equipment is a critical component of health infrastructure development, particularly in oncology services requiring radiotherapy technology. Specific Background: Dr. Soeradji Tirtonegoro General Hospital is constructing an Integrated Cancer Center financed through a foreign loan scheme under Islamic Development Bank regulations, where Linear Accelerator (LINAC) procurement must follow International Competitive Bidding procedures and the equipment type has not yet been determined. Knowledge Gap: Empirical studies examining how LINAC type determination and institutional coordination influence construction time performance through decision-making processes in specialized hospital projects remain limited. Aims: This study analyzes the role of LINAC equipment determination and institutional coordination in achieving project time performance in LINAC bunker construction. Results: Multiple linear regression using IBM SPSS 25 indicates that LINAC type determination is the most dominant factor affecting project time performance, supported by effective coordination in procurement planning and tender preparation. Implications: Timely technical decisions and coordinated procurement mechanisms are essential to prevent construction delays and minimize design adjustments. Highlights: Equipment specification selection was the strongest factor linked to schedule attainment in bunker construction. Institutional collaboration under foreign loan procedures shaped tender preparation and planning. Regression analysis confirmed the importance of managerial decisions in meeting construction timelines. Keywords: Linac Type Determination, Institutional Coordination, Project Time Performance, Decision-Making Performance, Medical Equipment Procurement